Plano de aplicação de um curso de formação de empreendedores destinado a pequenos negócios: meu negócio descomplicado - Silva, Lyanna Peixoto (2019)
This project focuses on the importance of understanding the needs and particularities of micro and small business management in the interior of the country, seeking ways to contribute to an improvement in the management and results of these companies. The basis for carrying out a survey to identify the main knowledge gaps and the best ways to effectively qualify this profile of entrepreneurs was a bibliography about entrepreneurship based mainly on the Ries and Baron & Shane precepts, as well as on the construction of knowledge , with Bates and Bligh as essential references. The results found in the exploratory and descriptive studies guide the proposal of an implementation plan of an entrepreneurs training course focused on small businesses.